Climate change impacts on lake thermal dynamics and ecosystem vulnerabilities. (11th November 2015) - Sahoo, G. B.; Forrest, A. L.; Schladow, S. G.; Reuter, J. E.; Coats, R.; Dettinger, M.
Abstract: Using water column temperature records collected since 1968, we analyzed the impacts of climate change on thermal properties, stability intensity, length of stratification, and deep mixing dynamics of Lake Tahoe using a modified stability index (SI). This new SI is easier to produce and is a more informative measure of deep lake stability than commonly used stability indices. The annual average SI increased at 16.62 kg/m 2 /decade although the summer (May–October) average SI increased at a higher rate (25.42 kg/m 2 /decade) during the period 1968–2014. This resulted in the lengthening of the stratification season by approximately 24 d. We simulated the lake thermal structure over a future 100 yr period using a lake hydrodynamic model driven by statistically downscaled outputs of the Geophysical Fluid Dynamics Laboratory Model (GFDL) for two different green house gas emission scenarios (the A2 in which greenhouse‐gas emissions increase rapidly throughout the 21 st Century, and the B1 in which emissions slow and then level off by the late 21 st Century). The results suggest a continuation and intensification of the already observed trends. The length of stratification duration and the annual average lake stability are projected to increase by 38 d and 12 d and 30.25 kg/m 2 /decade and 8.66 kg/m 2 /decade, respectively for GFDLA2 and GFDLB1, respectively during 2014–2098. The consequences of this change bear the hallmarks of climate change induced lake warming and possible exacerbation of existing water quality, quantity and ecosystem changes. The developed methodology could be extended and applied to other lakes as a tool to predict changes in stratification and mixing dynamics.